2018
DOI: 10.1111/cns.13002
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and cannabis use in college students are predicted by sex‐dimorphic interactions between MAOA genotype and child abuse

Abstract: These biosocial underpinnings of tobacco and cannabis use may prove important in the development of novel personalized preventive strategies for substance use disorders in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 145 publications
(355 reference statements)
3
19
0
1
Order By: Relevance
“…The present findings extend our previous report of sexdimorphic influences of G×E interactions in the lifetime use of tobacco (Fite et al, 2018) among college students. Furthermore, these results are consistent with previous evidence indicating sex differences in the interactive influence of these G×E interactions with respect to antisocial conduct (Nikulina et al, 2012;Stogner and Gibson, 2013;Byrd and Manuck, 2014;Harro and Oreland, 2016) and alcohol use (Nilsson et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present findings extend our previous report of sexdimorphic influences of G×E interactions in the lifetime use of tobacco (Fite et al, 2018) among college students. Furthermore, these results are consistent with previous evidence indicating sex differences in the interactive influence of these G×E interactions with respect to antisocial conduct (Nikulina et al, 2012;Stogner and Gibson, 2013;Byrd and Manuck, 2014;Harro and Oreland, 2016) and alcohol use (Nilsson et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…We recently showed that, among college students, tobacco and cannabis consumption is influenced by the interaction of child maltreatment and the gene MAOA, the X-linked gene encoding for monoamine oxidase A (Fite et al, 2018). In line with our report, Stogner and Gibson (2013) also documented that the interplay of this gene with lifetime stress increases the risk for initiation to alcohol and cannabis use in male adolescents.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…The MAO-A gene has a 30-base pair repeat in the promoter region that affects transcriptional efficiency [ 42 ]. The high-activity variant (MAOA-H; 3.5 or 4 repeats) has shown significant association with impulsive personality traits [ 43 ] and tobacco and cannabis use [ 44 ], but other studies have reported conflicting results, with the low-activity variant (MAOA-L; 2, 3, or 5 repeats) associated with disordered gambling [ 45 , 46 ]. However, considering the complexity of IA, to date there is a dearth of studies that have considered possible interactions between genetic vulnerability and the risk provided by the social environment [ 47 ], although recent evidence has highlighted the genetic moderation on the impact of the environment on other disorders and behaviors related to addiction [ 48 ].…”
Section: Introductionmentioning
confidence: 99%